The effect of assistive devices on writing speed and legilibility in grade two learning disabled children - Levin, Taryn Ann (My University, 2010)
The effect of assistive devices on the speed and legibility of a child’s writing is not fully understood in the literature. This study therefore investigated the effects of Stetro pencil grips, soft splints and inclined surfaces on handwriting speed and legibility in order to better guide occupational therapists with regard to handwriting intervention. A writing legibility score sheet was developed to measure the factors of handwriting requiring assessment in this study namely: letter formation, spacing between words, letter spacing between lines, accuracy and general appearance. The study also compared the handwriting speed and legibility of grade two learning disabled learners with grade two mainstream learners. In analysing the results, letter formation and general appearance were the two areas where the learning disabled sample scored significantly worse than the mainstream sample. The various assistive devices were shown to have different impacts on writing speed and the five areas of legibility.
MSc, Occupational Therapy, Faculty of Health Sciences, University of the Witwatersrand
Keywords: learning disabilities; children; grade two; writing speed; writing legibility